s-ketamine enhances thalamocortical and corticocortical synaptic transmission in acute murine brain slices via increased AMPA-receptor-mediated pathways - Bieber, Matthias; Schwerin, Stefan; Kreuzer, Matthias; Klug, Claudia; Henzler, Marie; Schneider, Gerhard; Haseneder, Rainer; Kratzer, Stephan (Frontiers in Systems Neuroscience, 2022)
Despite ongoing research efforts and routine clinical use, the neuronal mechanisms underlying the anesthesia-induced loss of consciousness are still under debate. Unlike most anesthetics, ketamine increases thalamic and cortical activity. Ketamine is considered to act via a NMDA-receptor antagonism mediated reduction of inhibition, i.e., disinhibition. Intact interactions between thalamus and cortex constitute a prerequisite for the maintenance of consciousness and are thus a promising target for anesthetics to induce loss of consciousness. In this study, we aim to characterize the influence of s-ketamine on the thalamocortical network using acute brain-slice preparation. We performed whole-cell patch-clamp recordings from pyramidal neurons in cortical lamina IV and thalamocortical relay neurons in acute brain slices from CB57BL/6N mice. Excitatory postsynaptic potentials (EPSPs) were obtained via electrical stimulation of the cortex with a bipolar electrode that was positioned to lamina II/III (electrically induced EPSPs; eEPSPs) or via optogenetic activation of thalamocortical relay neurons (optogenetically induced EPSPs; oEPSPs). Intrinsic neuronal properties (like resting membrane potential, membrane threshold for action potential generation, input resistance and tonic action potential frequency), as well as NMDA-receptor dependent and independent spontaneous GABAA-receptor mediated inhibitory postsynaptic currents (sIPSCs) were evaluated. Wilcoxon signed-rank test (level of significance < 0.05) served as statistical test, Cohen’s U3_1 was used to determine the actual effect size. Within 20 minutes, s-ketamine (5 µM) significantly increased both intracortical eEPSPs as well as thalamocortical oEPSPs. NMDA-receptor mediated intracortical eEPSPs were significantly reduced. Intrinsic neuronal properties of cortical pyramidal neurons from lamina IV and thalamocortical relay neurons in the ventrobasal thalamic complex were not substantially affected. Neither a significant effect on NMDA-receptor dependent GABAA sIPSCs (in the meaning of disinhibition), nor a reduction of NMDA-receptor independent GABAA sIPSCs were observed. Both thalamocortical and intracortical AMPA-receptor mediated EPSPs were significantly increased. In conclusion, our findings show no evidence for a NMDA-receptor antagonism-based disinhibition, but rather suggest an enhanced thalamocortical and intracortical synaptic transmission, which appears to be driven via increased AMPA-receptor mediated transmission.